Effect of kombucha butterfly pea (Clitoria ternatea) solution on Enterococcus faecalis biofilm - Yuanita, Tamara; Marpaung, Grace Julieta; Wiratno, Amelia Rahma; Wahjuningrum, Dian Agustin; Juniarti, Devi Eka (Conservative Dentistry Journal, 2025)
Background: Enterococcus faecalis is a facultative anaerobic bacterium that is often found in the root canals of teeth with pulp necrosis and is often the cause of endodontic treatment failure. On the other hand, the fermented beverage kombucha is made using a fermentation process by bacteria and yeast, known as SCOBY (Symbiotic Culture of Bacterial and Yeast). The fermentation process in kombucha causes a decrease in the pH of the medium, where the bacteria in the SCOBY convert sugar into ethanol and acetic acid. The butterfly pea flower (Clitoria ternatea) has single petals of purple, blue, pink, or white color and is proven to have antibacterial as well as antibiofilm properties. Purpose: To determine the effect of kombucha butterfly pea (Clitoria ternatea) solution on Enterococcus faecalis biofilm. Methods: Kombucha butterfly pea with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.56%, as well as NaOCl 2,5% was given Enterococcus faecalis biofilm. To determine biofilm formation, test tubes were washed, adherent cells were stained with 0.1% crystal violet, and light absorbance was measured with a spectrophotometer at a wavelength of 540nm. Results: The percentage of inhibitory power of kombucha butterfly pea against E. faecalis biofilm decreased gradually from concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.56%. The highest percentage of inhibition was in kombucha with butterfly pea with a concentration of 100% which is equivalent to 2,5% NaOCl as an antibiotic for root canal irigation. Conclusion: Kombucha of butterfly pea flower (Clitoria ternatea) can reduce the decrease in Enterococcus faecalis biofilm formation with a concentration of 12.5% designated as MBIC50 and a concentration of 100% designated as MBEC90.